2016
DOI: 10.1016/j.ptsp.2015.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Cervical range of motion, cervical and shoulder strength in senior versus age-grade Rugby Union International front-row forwards

Abstract: Objectives: To provide normative values for cervical range of motion (CROM), isometric cervical and shoulder strength for; International Senior professional, and International Age-grade Rugby Union front-row forwards.Design: Cross-sectional population study Setting: All international level front-row players within a Rugby Union Tier 1 Nation.Participants: Nineteen Senior and 21 Age-grade front-row forwards underwent CROM, cervical and shoulder strength testing.Main outcome measures: CROM was measured using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…Noteworthy is that these ratios are marginally greater than those presented elsewhere using different methods of testing (isokinetic and break test), wherein flexion-to-extension ratios in Rugby Union ranged, on average, from 0.65 to 0.7 [14,33]. Results of previous studies at different levels of competition have shown greater absolute values in extension compared to flexion in Rugby Union players [34][35][36], with younger players possessing lower strength ratios compared to senior players [17], and forwards exhibiting lower ratios than backs [19,33]. These imbalances in neck musculature are a potential risk factor for neck injuries, where flexion-to-extension ratio imbalances have been associated with higher head angular and linear accelerations in other cohorts [37].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Noteworthy is that these ratios are marginally greater than those presented elsewhere using different methods of testing (isokinetic and break test), wherein flexion-to-extension ratios in Rugby Union ranged, on average, from 0.65 to 0.7 [14,33]. Results of previous studies at different levels of competition have shown greater absolute values in extension compared to flexion in Rugby Union players [34][35][36], with younger players possessing lower strength ratios compared to senior players [17], and forwards exhibiting lower ratios than backs [19,33]. These imbalances in neck musculature are a potential risk factor for neck injuries, where flexion-to-extension ratio imbalances have been associated with higher head angular and linear accelerations in other cohorts [37].…”
Section: Discussionmentioning
confidence: 79%
“…Although the break test is the most common method used in Rugby Union, clinicians have expressed concerns regarding the 'aggressiveness' of this method and the potential to injure players during testing [12]. The resistance is applied to evoke a maximal muscle contraction in flexion, extension, and bilateral lateral flexion directions using a head harness attached to a cable and dynamometer or load cell until the initiation of the movement (i.e., positional failure) [11,[13][14][15][16][17]. Previous reliability studies with this neck strength assessment method demonstrate good-to-excellent intrarater and interrater reliability (intraclass correlation coefficient (ICC) 0.80-0.92) when implemented in seated or lying positions [11,18].…”
Section: Introductionmentioning
confidence: 99%
“…Measurements. The cervical range of motion was examined using the CROM goniometer [7,23,24]. The examinations were performed in a Spine Kinesiology facility.…”
Section: Methodsmentioning
confidence: 99%
“…A major limitation of this study is that the method of measuring neck strength is not well established and has not been published in the peer-reviewed literature. However, isometric neck muscle testing is well validated, 4,14,17,21,34,35 and this study's technique overcomes limitations of previous HHD methods relating to tester strength, 36 the potential for eccentric strength capture as per a "break contraction" method, 10,15 and maintaining a standardized head position compared with self-testing. 34 Reviewing the force output measured during this study, the players strength was similar to that of U18 school rugby players (mean ± 95% CI = 333.4 ± 79.4 N), which was a similar population.…”
Section: Strengths and Limitationsmentioning
confidence: 96%
“…Neck strength research involving U18 players has previously been limited to front-row players only. 10,16 Another strength of this study is the results are valid across elite age-group environments as "real-world" methodology was employed. For instance, the effects of the intervention occurred despite less than 100% adherence, reflecting that in real life, players miss training and thus do not receive the ideal training load as was intended.…”
Section: Strengths and Limitationsmentioning
confidence: 99%